Limited Regional Aerosol and Cloud Microphysical Changes Despite Unprecedented Decline in Nitrogen Oxide Pollution During the February 2020 COVID‐19 Shutdown in China - Diamond, Michael S.; Wood, Robert (Geophysical research letters, 2020)
Following the emergence of a novel coronavirus in Wuhan, China instituted shutdown measures starting in late January and continuing into February 2020 to arrest the spread of disease. This resulted in a sharp economic contraction unparalleled in recent Chinese history. Satellite retrievals show that nitrogen dioxide pollution declined by an unprecedented amount (~50% regionally) from its expected unperturbed value, but regional‐scale column aerosol loadings and cloud microphysical properties were not detectably affected. The disparate impact is tied to differential economic impacts of the shutdown, in which transportation, a disproportionate source of nitrogen oxide emissions, underwent drastic declines (~90% reductions in passenger traffic), whereas industry and power generation, responsible for >90% of particulate emissions, were relatively less affected (~20% reductions in electricity and thermal power generation). A combination of anomalously warm and humid meteorological conditions and complex chemical interactions further decreased nitrogen dioxide concentrations but likely enhanced secondary aerosol formation. Plain Language Summary To slow the spread of COVID‐19, China implemented strict policies limiting travel and public gatherings in February 2020, resulting in a pronounced economic decline. Satellite measurements show that levels of nitrogen oxides, gases that are a major component of air pollution, were substantially lower than what we would normally expect for February. Surprisingly, however, we did not observe any similar changes in airborne particles (another major component of air pollution) or in the size of cloud droplets (which is partly determined by the abundance of airborne particles). This is important because airborne particles, in addition to harming human health, affect the climate by changing how much sunlight is absorbed on Earth versus reflected back into space. The transportation sector of the economy was hit particularly hard by the coronavirus shutdown, but heavy industries and power plants were relatively less affected. Transportation is a major source of nitrogen oxides but not of airborne particles or their chemical precursors, which are mostly emitted by industry and power plants. The shutdown's much larger effect on transportation than on industry or power plants, along with changes in weather and chemical interactions, help explain the differences we see in the different types of air pollution. Key Points Rapid economic collapse in February 2020 due to the COVID‐19 pandemic and partial recovery in March 2020 are unique in recent Chinese history Regional decline in NO2 pollution is unprecedented in the satellite record, but no change in aerosol or cloud properties is detected Different economic impacts by sector, meteorology, and complex chemical interactions help explain differences in NOx and aerosol response